Venice According to Odyniec (and Mickiewicz?) in Romantic Contexts - Kurska, Anna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
This text is a reconstruction of the image of Venice offered in Listy z podróży by Antoni Edward Odyniec. Against the background of Romantic traditions (Byron, Chateaubriand, Shelley, and Radcliffe), I present how the author shaped the portrait of Venice suspended between the Romantic vision of the city/monster (Leviathan) and the ballad-based vision of the city/Siren. I indicate not only the fact that the image of Venice was rooted in the sentimental/Romantic stereotype, but I also define to what extent it was formed by the imagined world of Polish nobility, i.e. szlachta. Most of all, however, I am interested in the traces present in Listy z podróży which enable one to uncover Mickiewicz’s influence on how Odyniec shaped the image of Venice.